RISK FACTOR OF ECTOPIC PREGNANCY BY USING LITERATURE REVIEW METHOD - Winda Fatma Sari; Adityawarman Adityawarman; Budiono Budiono (UNIVERSITAS AIRLANGGA, 2021)
Background: Ectopic pregnancy is a pregnancy outside the uterus, embryo could attached to thefallopian tube, ovary cervix or cervix. Around 85-90% incidence of ectopic pregnancy is found inmultigravid women. According to data from the Health Office, maternal mortality in 2017 tendsto increase in the last two years. Not only it is a major predictor of mortality and morbidity inpregnant women, but individuals with a history of ectopic pregnancy have a greater risk. Thepurpose of this research was to determine the risk factors that cause ectopic pregnancy by usingliterature studies review. Method:This study used a systematic review of articles that publishedbetween 2013-2020 in the Science Direct, Scopus and Google Scholar. 10 articles that meet theinclusion and exclusion criteria, included as a sample for further review. The results regarding torisk factors that caused ectopic pregnancy in each article were systematically synthesized. Results:Risk factors found to be significantly associated with the incidence of ectopic pregnancy in thearticle were age (2), infertility (2), IUD (3), PID (3), Ectopic Pregnancy History (5), Progestine Pills (2), History of Abortion (1), Smoking (3). Conclusions: age, infertility, IUD, PID, history of ectopic pregnancy, progestine pill, History of abortion, and smoking were risk factors that hadsignificant relationship with the incidence of ectopic pregnancy.